EDUKASI OLAHRAGA BOLA VOLI MINI PADA ANAK DI DESA KARANG INDAH - Bangun, Farhan Fadilah Arya; Abidin, Dindin; Ridlo, Azi Faiz (An-Nizam, 2024)
The purpose of community service is by introducing mini volleyball in the classroom, students will be more interested in the sport and help in socializing it. Without strong student enthusiasm, volleyball will be difficult to market, especially to elementary school children. In order for a child to realize all his desires, including success in sports, every parent needs to have dreams. The purpose of this introduction is to demonstrate the skills of elementary school children, particularly in the game of volleyball. The advocacy method is the approach used in this research. The result of the community service that this program has successfully created an atmosphere of togetherness and cooperation among the children. Through the mini volleyball game, they learn about values such as teamwork, sportsmanship, and discipline. The social interactions established during practices and matches also strengthen the social bonds among participants, which have a positive impact on their relationships in the school and community environment.